2022
DOI: 10.1177/10556656221121062
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cleft Related-Genes may be Involved in Root Curvature of Maxillary Lateral Incisors

Abstract: The maxilla is formed by the medial nasal and maxillary processes fusion. The dental lamina develops from 2 origins connecting in the lateral incisor. The maxillary lateral incisor region is often affected by dental anomalies and clefting. It is possible that genes involved in oral cleft could also be associated with a variety of phenotypic variations in the maxillary lateral incisor. In this phenotype–genotype study, we explored the association between polymorphisms in the oral-cleft-related genes BMP2 and BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In our study, the left maxillary region was found to be the most common localization of both cleft and root dilaceration, contrary to the expected outcome. Although genetic studies have reported common genes associated with these root anomalies and clefts, current findings are still insufficient to explain the same localization (Küchler et al, 2022). On the other hand, Hereman et al (2018) reported that there is a great risk for canine impaction at the cleft side in unilateral CLP patients.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, the left maxillary region was found to be the most common localization of both cleft and root dilaceration, contrary to the expected outcome. Although genetic studies have reported common genes associated with these root anomalies and clefts, current findings are still insufficient to explain the same localization (Küchler et al, 2022). On the other hand, Hereman et al (2018) reported that there is a great risk for canine impaction at the cleft side in unilateral CLP patients.…”
Section: Discussionmentioning
confidence: 95%
“…We also investigated SNPs in BMP4 and SMAD6 genes due to their previous association with skeletal malocclusions [ 8 ]. BMP4 is well-known for its involvement in cell differentiation, bone development and the studied SNP rs17563 is involved in craniofacial phenotypes [ 30 ]. BMP4 signaling is complex, with potential cross-talks, including SMAD signaling.…”
Section: Discussionmentioning
confidence: 99%